2011
DOI: 10.1007/s11106-011-9345-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of titanium-aluminum alloys doped with niobium and tantalum

Abstract: melted in a laboratory arc furnace from pure components (~99.9 wt.%) are studied by X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), differential thermal analysis (DTA), and compression testing. The alloys are found to consist mainly of a superfine lamellar structure of decomposition β → α → α + γ → α 2 + γ and contain tiny islands of the γ phase and also the β phase at 12 at.% Nb or Ta. The CALPHAD approach is used to obtain a thermodynamic description of the Al−Nb−Ta−Ti s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Since phase diagrams describing phase transformations in the studied composites with chemical composition close to 8 at.% Nb, 1 at.% Mo, and 3.6 at.% C are not available, the solidification path and phase equilibria can be estimated based on phase diagrams reported for Nb-, Nb-Mo-, and C-doped TiAl-based alloys [38][39][40][41][42]. According to the ternary Ti-Al-C-phase diagrams [42], the cubic TiC 1−x -phase is formed as a primary solidification phase in the melt at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Since phase diagrams describing phase transformations in the studied composites with chemical composition close to 8 at.% Nb, 1 at.% Mo, and 3.6 at.% C are not available, the solidification path and phase equilibria can be estimated based on phase diagrams reported for Nb-, Nb-Mo-, and C-doped TiAl-based alloys [38][39][40][41][42]. According to the ternary Ti-Al-C-phase diagrams [42], the cubic TiC 1−x -phase is formed as a primary solidification phase in the melt at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This processed microstructure can vary sensitively by the post-HT. The solidification route of Ti-48Al-2Nb-2Cr (at%) during L-PBF follows the decomposition path of α→α + γ→α 2 + γ [ 19 ]. However, it has been observed that the final microstructure was dominated by α 2 phase, while the γ phase scarcely existed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors conducted chemical and mechanical analyses on several Al-Ti IMC to check their strength and ductility [2]. Others proposed diffusion welding of Ti and Al multi-laminated materials [3].…”
Section: Introductionmentioning
confidence: 99%